2015
DOI: 10.1097/mcg.0000000000000075
|View full text |Cite
|
Sign up to set email alerts
|

Low Awareness of Nonalcoholic Fatty Liver Disease Among Patients at High Metabolic Risk

Abstract: Among high metabolic risk individuals there is low awareness of NAFLD. The majority of those surveyed expressed interest in learning about NAFLD. These findings suggest opportunities to raise public awareness of NAFLD, particularly among patients at high metabolic risk, and to provide education to high-risk individuals with the goal of implementing early prevention strategies and optimizing care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
64
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(66 citation statements)
references
References 4 publications
2
64
0
Order By: Relevance
“…Taken together, this pattern of care reflects low disease awareness among patients and providers, even in the face of multiple metabolic risk factors. 21,22 These care patterns also reflect perceptions regarding the clinical significance and treatment options for NAFLD held by many providers. 23 This low rate of referral to GI/Hepatology is in line with data from prior studies where 71% of providers reported that they did not refer patients with suspected NAFLD to GI/Hepatology.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Taken together, this pattern of care reflects low disease awareness among patients and providers, even in the face of multiple metabolic risk factors. 21,22 These care patterns also reflect perceptions regarding the clinical significance and treatment options for NAFLD held by many providers. 23 This low rate of referral to GI/Hepatology is in line with data from prior studies where 71% of providers reported that they did not refer patients with suspected NAFLD to GI/Hepatology.…”
Section: Discussionmentioning
confidence: 91%
“…Also of note, an additional one third of NAFLD patients were under the care of a GI provider for other conditions (eg, acid reflux and diarrhoea), but they did not receive care related to NAFLD. Taken together, this pattern of care reflects low disease awareness among patients and providers, even in the face of multiple metabolic risk factors . These care patterns also reflect perceptions regarding the clinical significance and treatment options for NAFLD held by many providers .…”
Section: Discussionmentioning
confidence: 91%
“…Compounding the problem, patients with NAFLD, and especially those with metabolic disturbances, have low awareness of NAFLD and its complications and management. 59 Furthermore, a recent study assessed NAFLD management in primary care settings and noted that the magnitude and proportion of ALT elevation was the only predictor of NAFLD care and only 3% of those with high risk of fibrosis were referred to a specialist. 60 All these findings imply that prompt changes are needed in surveillance strategy, management, and education of both patients and primary care providers taking care of patients at high risk of NAFLD, especially those with T2DM.…”
Section: Discussionmentioning
confidence: 99%
“…About 10% of the specialists used drugs to treat these conditions that were not recommended by the current guidelines [10]. This striking unawareness was also evident in another survey of 302 US patients in an outpatient clinical setting where only 18% of respondents were familiar with NAFLD and 67% of these patients were unaware that they had metabolic risk factors [11].…”
mentioning
confidence: 99%